Development of a Multi-Sensor Mobile Device for Urban Air Quality Monitoring at the Street Corner: The SMILE Project - Jonas Pellegrino; Hassen Aziza; Mathieu Guerin; Pascal Taranto; Wenceslas Rahajandraibe; Blaise Ravelo (IEEE Access)
Air pollution is a critical contributor to the global climate change crisis and poses severe threats to human health worldwide. In this context, this paper introduces an innovative multi-sensor air quality monitoring (AQM) device designed to address the critical challenge of atmospheric pollution in urban environments. The AQM device features an optimized geometry specifically suited for mobility. It enables precise air quality (AQ) monitoring by measuring concentrations of NO2, O3, and CO, along with particulate matter (PM) across three size categories: PM1, PM2.5, and PM10. The AQM device ensures reliable operation across temperature variations from 10°C to 40°C and humidity levels ranging from 10% to 70%. Outdoor experiments were conducted in the city of Marseille to validate the efficiency of the AQM device and assess its ability to provide street-level air quality data. The AQM device was validated by comparing its measurements with data from four reference instruments (i.e., government-operated fixed stations) located within an 8 km radius of the center of Marseille. Real-time data is made available through a dedicated software server platform, offering geo-localized air quality information and detailed reports. The developed device offers excellent autonomy, with a full battery discharge lasting up to 28 hours, allowing it to be used throughout an entire day without the need for recharging. The proposed multi-sensor device was developed in the scope of the SMILE project (Self-calibrating air pollution Multi-sensors and ICDT platform to Leverage citizen’s Empowerment). The project aims to empower end users with the responsibility of carrying, activating, and monitoring their own sensor devices while utilizing specialized apps on their mobile phones.